Using the System Dynamic Approach to Develop a Policy Scenario for Reducing CO2 Emissions from Tourism Travel - SUSANTY, Aries; BAKTHTIAR, Arfan; PUSPITASARI, Nia Budi; PRASETYO, Siddiq (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019DO - 10.14505//jemt.10.3(35).10, 2019)
This study has several purposes. The first is to determine the causal relationship between tourist transportation behaviour, the number of tourists, and the volume of CO 2 emissions produced from tourist transportation to the Borobudur Temple. The second purpose is to use a system dynamic methodology to simulate a reduction in the amount of CO 2 emissions from tourist transportation to the Borobudur Temple. Lastly, to identify the best policy with which to regulate tourist transportation to the Borobudur Temple. To achieve those purposes, the r eal systems are identified and translated into system dynamic models using causal-loop and stock-and-flow diagrams. The model consists of three sub-systems, i.e., the number of tourists, the modes of transportation, and the volume of CO 2 emissions. Moreover, this study generated eight scenarios for comparison with respect to the volume of CO 2 emissions resulting from several transportation modes. The result of simulation with system dynamic methodology indicated that t he CO 2 emissions produced by scenarios 1, 2, 3, and 4 are within the range of 1,800,000 kg CO 2 , which means that they approach the target of reducing CO 2 emissions by 50% by 2035. This study provides essential insights for governmental and local authorities with respect to policy implementation.